A Tradition and Its Metamorphoses (1968–2024): Corporeality in Works by Octavio Paz, Ulises Carrión, And Rocío Cerón - Brocca, Josué (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
Throughout the twentieth and twenty-first centuries, the Mexican poetic tradition has changed its shape with its incorporation of avant-garde aesthetics and anti-traditional practices, producing a genealogy of texts that circle upon corporeality. This paper presents a diachronic analysis of a selection of works by three Mexican poets who, at different times, have explored this uncertain territory by transposing poetry to alternate media outputs with reflections on these themes: Octavio Paz, Ulises Carrión, and Rocío Cerón.